Complete chloroplast genome of an orchid species Cymbidium floribundum Lindl - Guo-Qiang Zhang; Zhong-Jian Liu; Si-Ren Lan (Mitochondrial DNA. Part B. Resources, 2019)
Cymbidium floribundum Lindl. is an ornamental plant and its native range is south China to north Vietnam. Here, we report the complete chloroplast (cp) genome sequence and the cp genome features of C. floribundum, which was assembled and characterized based on Illumina pair-end sequencing data. The complete chloroplast genome was 153998 bp in length. Its structure contained a large single-copy (LSC) region of 84,725 bp and a small single-copy (SSC) region of 19,009 bp, which were separated by a pair of extremely inverted repeats (IRs) of 25,132 bp each. The phylogenetic analysis indicated that C. floribundum was in the basal of subgenus Jenson.